Enhancing junior doctor confidence and competence in UGIB management: a three-cycle QIP using education, prescribing protocols and care bundles - Mareen Zachariah; Natalie Chan-Lam (Future Healthcare Journal, 2025)
Introduction: Upper gastrointestinal bleeding (UGIB) is a medical emergency requiring timely management. This quality improvement project (QIP) at Stepping Hill Hospital aimed to improve UGIB outcomes within 12 months by enhancing junior doctors’ confidence in recognition, assessment and management, with a secondary focus on coagulopathy. Methods: This three-cycle QIP followed the plan–do–study–act (PDSA) framework employing a mixed-methods approach. A driver diagram identified key management factors. • Cycle 1: delivered case-based teaching on variceal and non-variceal UGIB, covering guidelines, resuscitation and coagulopathy. • Cycle 2: based on Cycle 1 feedback, we refined materials and tailored teaching for FY1 doctors. We collaborated with gastroenterology pharmacists and the electronic prescribing and medicines administration (EPMA) team to implement an electronic prescribing protocol for variceal bleeds, improving prescribing consistency. • Cycle 3 (ongoing): updated local guidelines and incorporated an adapted British Society of Gastroenterology acute UGIB bundle, pending governance approval. Results: Pre- and post-intervention self-assessed confidence scores improved after each teaching session. Objective competence scores also improved, with 100% correctly identifying variceal bleed management after Cycle 2. All participants agreed that the EPMA protocol saved time, reduced prescribing errors and increased confidence. Additionally, 80% strongly agreed that a care bundle would improve adherence to critical management steps and best practices. Conclusion: Targeted teaching and integrated resources significantly improved confidence and competence in UGIB management. Embedding EPMA prescribing protocols and care bundles can create sustainable improvements in UGIB management. Future directions include developing simulation-based scenarios for immersive, team-based learning.